Penerapan Kesehatan dan Keselamatan Kerja Pada Aktivitas Transportasi Bus Penumpang Akap Diterminal Klari - Rizky Alwi Alamsyah; Aulia Fashanah Hadining; H. Wahyudin (Jurnal Ilmiah Wahana Pendidikan, 2021)
Intercity and Inter-Provincial Bus (AKAP) as a mode of mass transportation must meet Occupational Health and Safety (K3) requirements in various aspects. In addition to maintaining health and safety for all bus passengers and crew, the implementation of K3 serves to maintain the reliability of the transportation system. This study aims to determine the application of K3 to land transportation modes, namely AKAP passenger buses in Klari Terminal, Kab. Karawang. Qualitative descriptive research method, data collection techniques are carried out by observation, interview and documentation techniques. The implementation of the K3 program for AKAP passenger buses at Klari Terminal has been carried out according to the applicable standards, but for the facilities and infrastructure in the vehicle, all vehicles are suitable for operating according to the AKAP passenger bus standards.